Hadith #3826 - Sahih al-Bukhari - Subaia bint Al-Harith (Sahih al-Bukhari)
That she was married to Sad bin Khaula who was from the tribe of Bani ‘Amr bin Luai, and was one of those who fought the Badr battle. He died while she wa pregnant during Hajjat-ul-Wada.’ Soon after his death, she gave birth to a child. When she completed the term of deliver (i.e. became clean), she prepared herself for suitors. Abu As-Sanabil bin Bu’kak, a man from the tribe of Bani Abd-ud-Dal called on her and said to her, “What! I see you dressed up for the people to ask you in marria
Grade: Sahih